Encouraging girl child education in my village (Journal of Comparative Social Work, 2011)
My critical reflection will be drawn from an experience I had just a year after my graduation from the university where I was appointed as one of the X-students to lead a student cultural week in my village with the theme “raising awareness on education”. At the university, I was a member of my association in which students from my tribe generally come together to promote unity and encourage others in education. My role was to present a discourse on girl child education all the entire villagers who were gathered at the village square that evening. A high dropout rate at school and illiteracy are major problems in my region, in which there is still a great deal of gender disparity when it comes to educating children, especially the girl child. This programme is in line with the government’s policy of promoting education in my country, whose priority is for education to reach the grass-roots communities.